Use of Multiplex Real-Time PCR To Diagnose Scrub Typhus - Tantibhedhyangkul, Wiwit (J Clin Microbiol, 2017)
Scrub typhus, caused by Orientia tsutsugamushi, is a common cause of acute undifferentiated febrile illness in the Asia-Pacific region. However, its nonspecific clinical manifestation often prevents early diagnosis. We propose the use of PCR and serologic tests as diagnostic tools. Here, we developed a multiplex real-time PCR assay using hydrolysis (TaqMan) probes targeting O. tsutsugamushi 47-kDa, groEL, and human interferon beta (IFN-β gene) genes to improve early diagnosis of scrub typhus. The amplification efficiency was higher than 94%, and the lower detection limit was 10 copies per reaction. We used a human gene as an internal DNA quality and quantity control. To determine the sensitivity of this PCR assay, we selected patients with confirmed scrub typhus who exhibited a clear 4-fold increase in the level of IgG and/or IgM. The PCR assay result was positive in 45 of 52 patients, indicating a sensitivity of 86.5% (95% confidence interval [CI]: 74.2 to 94.4). The PCR assessment was negative for all 136 non-scrub typhus patients, indicating a specificity of 100% (95% CI: 97.3 to 100). In addition, this test helped diagnose patients with inconclusive immunofluorescence assay (IFA) results and using single blood samples. In conclusion, the real-time PCR assay proposed here is sensitive and specific in diagnosing scrub typhus. Combining PCR and serologic tests will improve the diagnosis of scrub typhus among patients presenting with acute febrile illness.